ASA C37.35-1962 : ASA American Standard Guide for the Operation and Maintenance of High Voltage Disconnecting Switches (IEEE, 1961)
High voltage disconnecting switches are assigned certain ratings by the manufacturer and standard tests are conducted to assure the user that the switch, when new, will perform within the ratings shown on the nameplate. It should be recognized that the switch in service will perform within these ratings only if properly operated and maintained. It cannot be stressed too strongly that prescribed safety rules should be adhered to at all times when operating or maintaining high voltage disconnecting switches near energized equipment or conductors.
Keywords: High voltages.; Electrical engineering.